HUMAN IMAGE IN CLASSICAL ISLAM AND SUFISM: PHILOSOPHICAL ANALYSIS - M. V. Nesprava (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The study aims to obtaine data about the human image in Islam through thought of the respective visions of both the classical directions of the Muslim religion and the attitudes of Islamic mysticism (Sufism). Achievement of this goal involves the application of methods such as philosophical analysis, comparative method, phenomenology, as well as the consistent solution of the following tasks: a) to analyze the main manifestations of anthropological ideas in Islam; b) to comprehend the specificity of Muslim ideas about a human in comparison with the corresponding Christian teaching; c) to consider disagreements between the interpretation of the essence and tasks of a human in the classical Islam and Sufism. Theoretical basis. The author proceedes from the unsatisfactory nature of the superficial interpretation of the human image in Islam, according to which a human is often expounded as a «slave of Allah», neglecting the multidimensionality of the metaphysical status of a human in Islam, as well as the polyparadigmality of the human image in various Islam directons. Originality. The author refines the human image in Islam in two aspects: first – in the aspect of his conceptual content and secondly – in the aspect of his paradigmatic diversity. Conclusions. The widespread beliefs among the researchers concerning the anthropological component of Islam are not sufficiently substantiated, since they often do not take into account the ambiguity and multidimensionality of the ideas of the Muslim religion towards a human. As it has been shown, the general Muslim ideas about the metaphysical status of a human include two dimensions – a human is interpreted as «the slave of Allah», as well as "the vicegerent of Allah". Within this perception of the human nature there are two various paradigms for interpreting the sphere of preferential fulfillment of a human's duties as the slave and the vicegerent. The first one is used by the classical Islam, it was called the externalistic paradigm. The internalistic paradigm is used by Sufism. The author presents that the theme of the human image in Islam is still not sufficiently studied and it requires further research. The comprehension of the existing in Salafist and Shiite varieties of Islam concerning the human nature interpretation and their essence and tasks are the most productive areas of such further research.